Implementasi Sistem Pembelajaran Daring di Masa Pandemi COVID-19 pada Koordinator Wilayah Talang Kelapa (Studi Kasus SMP Negeri 1 Talang Kelapa) - Rachmawati, Rachmawati; Nawawi, Effendi; Iriani, Atrika (Program Studi Magister Ilmu Administrasi Publik STISIPOL Candradimuka, 2022)
The implementation of the online learning system at the Talang Kelapa Region Coordinator, especially SMP Negeri 1 Talang Kelapa, has generally been running smoothly in the past few weeks. However, over time, many problems have arisen, such as complaints about teachers’ tasks being too much and complaints about internet quota and internet network problems. This study aims to identify and analyze the implementation of online learning systems during the COVID-19 pandemic at the Talang Kelapa Region Coordinator. This research is descriptive research with qualitative approach. The data collection techniques used were observation, interviews and documentation. Based on the results of the study, it is known that the implementation of the online learning system during the COVID-19 Pandemic at the Talang Kelapa Region Coordinator, especially SMP Negeri 1 Talang Kelapa, has shown good results, and runs effectively and smoothly in the implementation of this online learning system, teachers use WhatsApp more often. to communicate with students and their parents and to share information related to learning materials. Meanwhile, in the implementation of the online learning system, the teacher uses Zoom to deliver material and can provide students' understanding of the material being taught. The online learning system of the zoom application and WhatsApp social media indirectly has the ability to use and access technology increasingly controlled by students and teachers, and the Government provides study quota assistance in accordance with the needs of schools in the on-line learning system during the COVID-19 pandemic.